Online Marketing Strategy On Purchasing Decisions At Small And Medium Enterprises (UKM) Snack Barokah Bengkulu - Putra, Agung Pratama; Irwanto, Tito; Abi, Yudi Irawan; Putra , Iswidana Utama (Utami Publisher, 2025)
A widely used marketing strategy is the marketing mix. The marketing mix refers to the types of decisions that are made when marketing a product or service to consumers. The marketing mix also applies in online marketing, although the decisions made in online marketing may differ from traditional marketing. The purpose of this study is to identify factors that can influence and become elements of the preparation of marketing strategy Snack Barokah, compile and recommend the right marketing strategy to applied to Usaha Snack Barokah in an effort to expand the market and determine the priority order of strategies that can be applied in marketing products Snack Barokah in an effort to expand the market. The results showed that the instrument used in this study was a questionnaire, which consisted of 8 questions for the online marketing variable (X), 8 questions for purchasing decisions (Y), with a total of 80 research respondents. The research questionnaire contains a description of the respondents and answers to the questions given. The characteristics of respondents in this study are based on gender, age, latest education, occupation and number of visits per month.